Inflammatory Signalings Involved in Airway and Pulmonary Diseases - I-Ta Lee; Chuen-Mao Yang (Mediators of Inflammation)
In respiratory diseases, there is an increased expression of multiple inflammatory proteins in the respiratory tract, including cytokines, chemokines, and adhesion molecules. Chemokines have been shown to regulate inflammation and immune cell differentiation. Moreover, many of the known inflammatory target proteins, such as matrix metalloproteinase-9 (MMP-9), intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), cyclooxygenase-2 (COX-2), and cytosolic phospholipase A2 (cPLA2), are associated with airway and lung inflammation in response to various stimuli. Injuriously environmental stimuli can access the lung through either the airways or the pulmonary and systemic circulations. The time course and intensity of responses by resident and circulating cells may be regulated by various inflammatory signalings, including Src family kinases (SFKs), protein kinase C (PKC), growth factor tyrosine kinase receptors, nicotinamide adenine dinucleotide phosphate (NADPH)/reactive oxygen species (ROS), PI3K/Akt, MAPKs, nuclear factor-kappa B (NF-κB), activator protein-1 (AP-1), and other signaling molecules. These signaling molecules regulate both key inflammatory signaling transduction pathways and target proteins involved in airway and lung inflammation. Here, we discuss the mechanisms involved in the expression of inflammatory target proteins associated with the respiratory diseases. Knowledge of the mechanisms of inflammation regulation could lead to the pharmacological manipulation of anti-inflammatory drugs in the respiratory diseases.